KEDUDUKAN DAN TUJUAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Su’dadah Su’dadah (Jurnal Kependidikan, 2014)
The role of education is very crucial, especially when focused on the efforts to develop its positive potentials of human beings. Through the education process positive potentials of human beings are expected to create motivation and creativity that can result in a number of activities such as thinking (science) and creating new findings in various fields. Thus man can make himself as being cultured and civilized. To achieve this purpose, the education process should always be directed to developm individual potentials, so that human beings are able to understand and know their identity and responsibility as a living creature. Peran pendidikan menjadi amat krusial, terutama apabila dititikberatkan pada upaya untuk mengembangkan potensi positifnya. Potensi positif yang dimiliki manusia itu melalui proses pendidikan diharapkan dapat menciptakan motivasi dan daya kreasi yang dapat menghasilkan sejumlah aktivitas berupa pemikiran (ilmu pengetahuan), merekayasa temuan-temuan baru dalam berbagai bidang. Dengan demikian manusia dapat menjadikan dirinya sebagai makhluk yang berbudaya dan berperadaban. Untuk mencapai maksud tersebut proses pendidikan harus selalu diarahkan pada usaha pengembangan potensi individu, sehingga manusia tersebut sampai dapat memahami dan mengetahui jati diri dan tanggung jawabnya sebagai mahluk hidup.